Sacred toponyms of Tuva: lexical and semantic groups - Suvandii, Nadezhda D. (The New Research of Tuva, 2024)
The article analyzes the names of sacred toponyms in Tuva, which are places or natural objects revered by the Tuvan people as having special power. Some of these names directly contain terms related to holiness, while others do not, but they do contain other terms that indirectly indicate a sense of sacredness. The research was based on the geographical names of certain sacred toponyms, as well as information gathered from residents of the area through scientific expeditions in the Republic of Tuva. The author also drew on personal memories from the older generation of their family, who were native to the village of Don-Teresin in the Barun-Khemchik district. When analyzing the names, several lexical and semantic groups were considered: names of sacred springs, rivers, lakes, names of sacred passes and hills, names of religious camps, and names of forest areas. Examples were given for each group, along with explanations from residents and descriptions of the characteristics of these places.